EKSTRAKSI DAN KARAKTERISTIK FISIK-KIMIA EKSTRAK KASAR POLISAKARIDA LARUT AIR (PLA) DARI TEPUNG BIJI DURIAN (Durio zibhetinus Murr) - Herlina, Herlina; Djumarti, Djumarti; Yuli Andika, Evan (ROTOR, 2013)
Seed durian flour (Durio zibethinus Murr) is the waste from durian fruit wich are potential to becomewater soluble polysaccharides (WSP) source beause it contains gum. Seed durian process to seed durianflour is a method to avoid damaged material. The The research was aimed to obtained optimum extractionabout the yield of crude extract water soluble polysaccharides (WSP) from seed durian flour i.e ratiomaterial and solvent 1:5; 1:10; 1:15, extraction temperature at 30; 40; 50o C, speed sentrifuges spin7000; 10.000; 13.000 rpm; ratio supernatant and ethanol 1:3; 1:4; 1:5, extraction time for 0, 1, and 2 hrs,along with to characterize crude extract water soluble polysaccharides (WSP) from seed durian flour. theresults showed that highest extraction yield was obtained in combination with 1:10 of ratio material andsolvent, 50 Â°C of extraction temperature,13.000 rpm of speed sentrifuges spin, 1:4 of ratio supernatantand ethanol, and 2 hrs of extraction. It yielded WSP of 3,56%, brigthness (L) of 49,32. This WSP containedwater, ash, fatty, protein, carbohydrate, and total sugar of 13,86%, 12,48%, 1,78%; 19,76%, 65,98 and 61,23% respectively.Â Keywords: Water soluble polysaccharides, extraction, seed durian flour